The perinatal outcome in pregnancies with Novel Corona Virus 19 infection - A pilot study - Sujatha Ramabhatta; Asfia Banu; Asima Rubina; Sameena Bano; Misba Khalandar (Al Ameen Medical College, 2021)
Introduction: All over the world, life has been drastically altered due to Novel Corona Virus 19 (Covid-19) infection. As of today, nearly 39 million people are affected with a mortality of 3%. In India, the total number of cases have crossed 5 million with a mortality of 1.7%. This study was taken up to assess the effect of Covid-19 infection during pregnancy and neonatal outcome. Material and Methods: This study was done at Shifaa Hospital, Bangalore from June to August, 2020. Two hundred and ten mothers delivered babies with three sets of twins. Of these 210 mothers, 51 tested positive for Covid-19. Mode of delivery was documented. APGAR score, gestational age and weight of the newborns were noted. All asymptomatic neonates were shifted towards the mother side and breastfed. Symptomatic neonates were admitted to the NICU. Covid-19 swabs were taken for 37 neonates belonging to Covid-19 positive mothers between 24 to 48 hours of life. Repeat swabs at day 8 to day 10 were suggested. All the neonates were followed up after day 14. Results: The incidence of Covid-19 positivity was 24.28% among pregnant ladies. Majority of the mothers were asymptomatic with only 2 mothers having influenza like symptoms (ILI). The rate of caesarean section was higher compared to normal vaginal delivery. The mean birth weight of the babies in Covid-19 positive mothers was significantly lower than that of the Covid-19 negative mothers. Out of the 37 neonates tested for Covid-19, 3 were positive but remained asymptomatic at 14 day follow up. Thirty five neonates of the total 210 deliveries required NICU admission. Six neonates born to Covid-19 positive mothers were admitted in the NICU, out of which five had transient tachypnoea which resolved within 24 hours. Fifty neonates were born low birth weight, fifteen of them being born to the Covid-19 positive mothers. All babies were asymptomatic at follow up after 14 days. Conclusion: In our study, Covid-19 infection had no significant effect either on pregnancy or on the neonate except for a marginal decrease in the birth weight of the neonates of the Covid-19 positive mothers.